Import Competition, Formalization, and the Role of Contract Labor - Pavel Chakraborty; Rahul Singh; Vidhya Soundararajan (Institute of Labor Economics (IZA), 2022)
Does higher import competition increase formalization and aggregate productivity? Exploiting plausibly exogenous variation from Chinese imports, we provide empirical causal evidence that higher imports increases the share of formal manufacturing enterprise employment in India. This formal share increase is both due to the rise in formal-enterprise employment driven by the high productivity firms, and a fall in informal-enterprise employment. The labor reallocation is enabled by the formal firms' hiring of contract workers, who do not carry stringent string costs. Overall, Chinese import competition increased formal sector employment share by 3.7 percentage points, and aggregate labor productivity by 2.87%, between 2000-2001 and 2005-2006.
Keywords: F14; F16; O17; O47; F66; 330; import competition; formal sector employment; informality; contract workers; Chinese imports; reallocation; misallocation